2021
DOI: 10.1111/jfd.13479
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the different roles of T6SSs in pathogenicity of Pseudomonas plecoglossicida NB2011

Abstract: Pseudomonas plecoglossicida, the causative agent of visceral granulomas in the large yellow croaker (Larimichthys crocea) in China, encodes three sets of type Ⅵ secretion systems (T6SS1‐3). The purpose of this study was to characterize the different roles of T6SSs involved in infection. In‐frame deletion of T6SSs was constructed, which resulted in 8 mutants. Competition against E. coli DH5α, virulence against the croaker and in vivo survival ability of the mutants were tested. The expression and secretion of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Similar results were revealed by Jin et al. (2021), and further work demonstrated that T6SS2 and T6SS3 are involved in host infection, as combined deletion of both T6SS2 and T6SS3 or all three systems almost abolished the bacterial virulence (Jin et al. 2021).…”
Section: Virulence Factors/genes Of the Pathogensupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results were revealed by Jin et al. (2021), and further work demonstrated that T6SS2 and T6SS3 are involved in host infection, as combined deletion of both T6SS2 and T6SS3 or all three systems almost abolished the bacterial virulence (Jin et al. 2021).…”
Section: Virulence Factors/genes Of the Pathogensupporting
confidence: 79%
“…The T6SSs were demonstrated to play important roles during infection: T6SS1 mutation was found to abrogate most of the virulence against croakers, with no visceral granulomas developing in the infected fish (Tao et al 2020); and T6SS2 majorly contributed to bacterial competition (Li et al 2022a). Similar results were revealed by Jin et al (2021), and further work demonstrated that T6SS2 and T6SS3 are involved in host infection, as combined deletion of both T6SS2 and T6SS3 or all three systems almost abolished the bacterial virulence (Jin et al 2021). Knockdown of clpV or impB, which are T6SS ATPase-encoding genes, also resulted in strongly attenuated pathogen virulence (Luo et al 2019a;Liu et al 2020), verifying the essential roles of T6SSs during infection.…”
Section: Virulence Factors/genes Of the Pathogenmentioning
confidence: 55%
See 1 more Smart Citation
“…Bacterial virulence is usually affected by environmental factors. For example, the pathogenic temperature of “visceral white spot disease” caused by P. plecoglossicida in large yellow croaker and other commercial fish is 15°C–20°C ( Zhang et al., 2018a ; Kaur et al., 2019 ; Lv et al., 2019 ; Huang et al., 2020a ; Hu et al., 2021 ; Jin et al., 2021 ). The results of various stress experiments showed that compared with 18°C, the expression level of fusA was significantly downregulated at 4°C, 12°C, and 37°C.…”
Section: Discussionmentioning
confidence: 99%